Antagonistic effects of thiamine versus lead acetate exposure-correlated with hepato-renal toxicity in diabetic and non-diabetic rats: A stereological and biochemical survey - Rahmat Allah Fatahian Dehkordi; Tahereh Behbahani; Behnaz Karimi; Mohammad Shadkhast (Shahrekord University of Medical Sciences, 2023)
Background and aims: The present study aimed to investigate the protective effect of thiamine on the toxicity of lead acetate (PbAc) in the liver and kidneys of diabetic rats. To evaluate the effect of thiamine, stereological criteria, and biochemical processes were used. Methods: Forty-eight female rats were used and divided into eight groups of six animals. G I: served as the control group; G II: diabetic group; G III: PbAc group; G IV: thiamine group; G V: diabetes + thiamine group; G VI: PbAc + thiamine group; G VII: diabetes + PbAc + thiamine group; G VIII: diabetes + PbAc group. Results: The total volume of hepatocytes in the liver and the volume of cortex, medulla, and glomerulus in the kidney were significantly increased in the both diabetic and PbAc groups compared to control animals. Moreover, the sinusoids and central vein volumes showed a significant decrease in both the diabetic and PbAc groups compared with the controls. The PbAc and diabetic groups showed higher total cholesterol (TC), very low-density lipoprotein cholesterol (VLDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), malondialdehyde (MDA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine (Cr), and lower high-density lipoprotein cholesterol (HDL-C) concentrations than the control group. It was discovered that thiamine significantly alters the levels of the desired parameters, bringing them closer to the control group. Conclusion: Thiamine is a potent antidiabetic agent, and this compound supplementation possesses hypoglycemic properties and has an effect on the hepatorenal structure in diabetes rats.